Multiport Talkative Power Conversion: Basic Principle and System Modeling for Multiple-Active-Bridge Converters - Peter A. Hoeher; Yang Leng; Rongwu Zhu (IEEE Open Journal of Power Electronics)
Talkative Power Conversion (TPC) is a simultaneous information and power transfer technique, in which data modulation is integrated into a switched-mode power electronics converter. In this paper, to our best knowledge, for the first time TPC is applied to multiple-active-bridge converters with an arbitrary number of ports. This concept, called multiport TPC, extends potential use cases of multiport converters by embedded communication services. The add-on is purely software-based. The fundamentals of classical multiport converters are briefly reviewed and the basics of multiport TPC are presented. A combined signal and system model is derived for isolated H-bridge based multiport converters and can be applied to arbitrary port configurations, power modulation schemes, and data modulation schemes. For selected triple-active-bridge configurations, numerical results are presented and verified experimentally. Potential applications are suggested and future research perspectives are outlined.